The Gombe Ecosystem Health Project: 16 years of program evolution and lessons learned. Issue 4 (5th July 2021) - Lonsdorf, Elizabeth V.; Travis, Dominic A.; Raphael, Jane; Kamenya, Shadrack; Lipende, Iddi; Mwacha, Dismas; Collins, D. Anthony; Wilson, Michael; Mjungu, Deus; Murray, Carson; Bakuza, Jared; Wolf, Tiffany M.; et al.
Abstract: Infectious disease outbreaks pose a significant threat to the conservation of chimpanzees ( Pan troglodytes ) and all threatened nonhuman primates. Characterizing and mitigating these threats to support the sustainability and welfare of wild populations is of the highest priority. In an attempt to understand and mitigate the risk of disease for the chimpanzees of Gombe National Park, Tanzania, we initiated a long‐term health‐monitoring program in 2004. While the initial focus was to expand the ongoing behavioral research on chimpanzees to include standardized data on clinical signs of health, it soon became evident that the scope of the project would ideally include diagnostic surveillance of pathogens for all primates (including people) and domestic animals, both within and surrounding the National Park. Integration of these data, along with in‐depth post‐mortem examinations, have allowed us to establish baseline health indicators to inform outbreak response. Here, we describe the development and expansion of the Gombe Ecosystem Health project, review major findings from the research and summarize the challenges and lessons learned over the past 16 years. We also highlight future directions and present the opportunities and challenges that remain when implementing studies of ecosystem health in a complex, multispecies environment. Abstract : Chimpanzee Fifi during the outbreak of sarcoptic mange (left) and her juvenile son, Faustino, who was not severely affected. Fifi fully recovered from the outbreak, but her infant son (not pictured) was one of three infants to die during the outbreak. Photo by Anne Pusey. Research Highlights: Infectious diseases pose a significant threat to the conservation of nonhuman primates. We began a health‐monitoring program in 2004 to understand and mitigate the risk of disease for chimpanzees at Gombe National Park. We describe the expansion of the project over 16 years beyond chimpanzees and beyond the National Park and review major findings and lessons learned.